Gender and Religion: A Discourse Analysis of Gender Roles and Status Across Religious Perspectives - Wendi Silitonga; Ayu Syahfitri; Johannes Hasibuan; Cindy Septia (Journal of Gender and Millennium Development Studies, 2026)
Background: Gender inequality is often legitimized through religious interpretations, even though religions fundamentally promote the value of equality.Objective: This study aims to analyze the construction of gender discourse from a religious perspective and to identify forms of equality and the challenges that arise in practice. Method: This study employs a qualitative approach using gender discourse analysis through a literature review of religious texts and academic sources. The analysis was conducted through stages of data reduction, thematic categorization, power relation analysis, and critical interpretation. Results: All religions examined in this study possess normative foundations that support gender equality in spiritual, social, and moral dimensions. However, social practices remain influenced by patriarchal culture, as reflected in the restriction of women’s roles, male dominance in leadership, and bias in the interpretation of religious teachings. Conclusion: Religion plays an ambivalent role as both a source of legitimization and a driver of social transformation toward gender justice. Contribution: This study contributes to strengthening a contextual and inclusive reinterpretation of religion as an effort to promote more equitable gender relations.